Hybrid Cryptosystem Algorithm Vigenere Cipher and Base64 for Text Message Security Utilizing Least Significant Bit (LSB) Steganography as Insert into Image - Achmad Fauzi; Husnul Khair; Nasution, Raja Imanda Hakim (Yayasan Kita Menulis, 2023)
Security message text is aspect important in modern communications for guard privacy and confidentiality information. Without exists guarantee security, of course just can raises risk when sensitive and valuable information are accessed by unauthorized persons responsible answer. Cryptography and steganography is two field used in a manner wide For reach objective this. Algorithm Vigenere Cipher and Base64 are method used for encryption message text and Least Significant Bit (LSB) steganography was used as method for insert message encrypted to in image. LSB makes use of the last bits from pixels image for keep information addition without bother image visual display in a manner significant. With utilise method here, order encrypted can hidden in a manner confidential in image that looks normal. This hybrid cryptosystem combine excess from third algorithm such, ie speed and effectiveness encryption use algorithm Vigenere Cipher as well ability Base64 characteristics, and levels security message more increase.